The first recording of the wilt of the Hendersonian branches On the ficus sp (Ficus) in Iraq and its bio-control - muqdad aldarraji; Fadel Hassan Yasin (Al-Qadisiyah Journal of Pure Science, 2021)
The results of isolation and diagnosis from the samples of the ficus from Saladin Governorate are Samarra, Samara University, Balad and Dhuloiya. The disease was caused by Hendersonula torulidea Nattrass, which was isolated from all samples by 100%. Ficus plant in Iraq..The isolates did not differ in the daily growth rate and their dimensions on the PDA medium. Pathogenicity tests showed that isolates from the studied areas showed a significant increase in the severity of the disease. The isolates ranged between 80% and 75% respectively, whereas in the comparison treatment, it was 0%.The control factor Tricoderma harzianum and Bacillus subtilis showed high efficiency in plant protection from infection, reducing the severity of the disease to 25% and 40% of the sequence compared to the treatment of fungus alone, which was 95% severity of the disease..It also resulted in an increase in the dry weight of the vegetative total of Tricoderma. harzianum and Bacillus subtilis with pathogenic fungus 5.6 and 3.03 g / plant respectively. The dry vegetative weight in the comparison treatment with isolating pathogenic fungi alone was 1.40 g / plant..